2016
DOI: 10.1007/s10584-016-1603-7
|View full text |Cite
|
Sign up to set email alerts
|

How climate metrics affect global mitigation strategies and costs: a multi-model study

Abstract: In climate policy, substitutions metrics are used to determine exchange ratios for different greenhouse gases as part of a multi-gas strategy. The suitability of the metric depends on the policy goals and considerations regarding its practical use. Here, we present a multimodel comparison study to look at the impact of different metrics on the mitigation strategies and global climate policy costs. The study looks into different Global Warming Potentials (GWP) and the Global Temperature change Potential (GTP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…They indicated that the policy costs for reaching these two policy targets are roughly the same; however, they should be remarkably lower than the corresponding costs for achieving the global warming-rise goal of 2°C warming-rise goal, and this is in agreement with the relative finding in Tavoni et al (2014). Furthermore, climate metrics, like global warming potentials and global temperature change potential, may also play a significant role in the mitigation strategies and policy costs (Harmsen et al 2016).…”
Section: No Of Modelsmentioning
confidence: 59%
“…They indicated that the policy costs for reaching these two policy targets are roughly the same; however, they should be remarkably lower than the corresponding costs for achieving the global warming-rise goal of 2°C warming-rise goal, and this is in agreement with the relative finding in Tavoni et al (2014). Furthermore, climate metrics, like global warming potentials and global temperature change potential, may also play a significant role in the mitigation strategies and policy costs (Harmsen et al 2016).…”
Section: No Of Modelsmentioning
confidence: 59%
“…Previous studies showed that the use of GWP100 does lead to some but not a strong disadvantage in terms of global total abatement costs under stabilization pathways (including small overshoot pathways) ( 25 28 , 53 – 55 ). While we confirm this finding { Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S9 and S10). The high costs associated with the use of long time horizon metrics including GTP100 are due to the need for more CO 2 abatement at a higher cost to compensate for CH 4 emissions valued low ( 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations